Short-term effect of physical activity on sleep health: A population-based study using accelerometry - Andrea Wendt; Inácio Crochemore M. da Silva; Helen Gonçalves; Ana Menezes; Fernando Barros; Fernando C. Wehrmeister (Elsevier, 2022)
Background: Regular physical activity (PA) is an important behavior in improving sleep health. However, the short-term effects of PA on sleep are still controversial. This study aimed to verify the effect of different intensities of PA practiced in different periods of the day on the subsequent sleep night in a population-based cohort of young adults. Methods: : Prospective analyses were conducted for PA performed during the day and its effect on the following sleep night using data from the 22-year follow-up of the 1993 Pelotas Birth Cohort in Brazil (mean age of participants = 22.6 years). Wrist-worn accelerometry was used to measure both PA and sleep parameters. Regarding intensity, we analyzed the sleep effect of light PA (LPA), moderate PA, and vigorous PA, stratified by sex. Sleep variables were sleep time window (STW; the difference between sleep onset and sleep end), total sleep time (TST; the sum of minutes classified as sleep in STW), and sleep percent (SP; SP = (TST/STW); expressed in percentage). We performed generalized estimating equations using Stata software. Results: : The means of STW, TST, and SP were 443.6 min/day, 371.1 min/day, and 84%, respectively. Time spent in moderate PA and vigorous PA in the morning and afternoon was not associated with sleep variables. Among men, 10 min/day of morning LPA increased TST by 2.56 min/day. Among women, 10 min/day of morning LPA increased SP by 0.15 percentage points. Afternoon LPA also increased SP by 0.09 percentage points for women. Night PA seems to have an inverse effect on sleep variables for any intensity and both sexes. Conclusion: : The effect of PA on sleep health is intrinsically related to the period of the day in which it is performed. The effect magnitude is different between sexes. For better sleep health, it is preferable that PA be performed during the day.